Simulation of airflow at Vernadsky station for multi-site damage identification - Tsybulnyk, S.; Komenchuk, I.; Tymchenko, A. (Український антарктичний журнал, 2017)
Relevance of the study is that the consequences of premature destruction of the fuel tank or the wall of the building of the Ukrainian Antarctic Akademik Vernadsky station (Vernadsky station) may result in significant financial costs and human lives as a result of multi-site damage. Therefore, the main objective of the study is to identify the most probable places of snow accumulation and maximum wind pressure zones for identification and prevention of multi-site damage of buildings and engineering structures. Актуальність роботи полягає в тому, що наслідками передчасного руйнування паливного бака або стіни будівлі Української антарктичної станції «Академік Вернадський» внаслідок багатоосередкового пошкодження можуть бути значні фінансові витрати і людські життя. Тому метою роботи є виявлення найбільш ймовірних місць скупчення снігу та зон максимального тиску вітру для ідентифікації та запобігання багатоосередкового пошкодження будівель та інженерних конструкцій. Актуальность работы заключается в том, что последствиями преждевременного разрушения топливного бака или стены здания Украинской антарктической станции «Академик Вернадский» вследствие многоочагового повреждения могут быть значительные финансовые затраты и человеческие жизни. Поэтому целью работы является определение наиболее вероятных мест скопления снега и зон максимального давления ветра для идентификации и предотвращения многоочагового повреждения зданий и инженерных сооружений.